Analysing of financial literacy among self-owned oil palm farmers in the tidal land environment of Barito Kuala Regency, South Kalimantan - Azis, Yusuf; Hartoni, Hartoni; Shafriani, Karimal Arum; Gogoi, Jeemoni (Journal of Agricultural Socio-Economics (JASE), 2024)
This study aims to assess the level of financial literacy and examine the influencing factors among independent oil palm smallholders operating in the tidal land areas of Barito Kuala Regency, South Kalimantan, Indonesia. Despite the region's significant agricultural potential, particularly in oil palm cultivation, local farmers often face financial vulnerability due to limited financial knowledge. Using a sample of 100 respondents selected through simple random sampling across Wanaraya, Tamban, and Barambai Districts, the study evaluates financial literacy based on the Organisation for Economic Co-operation and Development (OECD) framework and applies binary logistic regression to identify key determinants. The Wald test analysis confirms that income, formal education, proximity to financial institutions, and individual risk preferences significantly influence financial literacy among the respondents. Specifically, higher income and more years of formal education are associated with increased likelihood of being financially literate. A shorter distance to financial institutions also positively affects literacy, suggesting that physical access to financial services supports better financial understanding. Additionally, individuals with higher risk preferences tend to have greater financial literacy, potentially due to increased engagement with financial decision-making. Conversely, age was found to have no significant effect, which confirms that financial literacy is not inherently tied to a person’s age or life stage. Instead, it is determined by exposure to financial knowledge, access to resources, and engagement with financial practices, factors that vary regardless of age. While the study is limited by its regional scope and sample size, it offers critical insights for policymakers and stakeholders in promoting targeted financial education programs for rural agricultural communities. The findings emphasize the need for accessible, context-specific financial literacy initiatives to enhance the economic resilience of smallholder farmers in underdeveloped regions.